Proteomic study of recombinant escherichia coli expressing beauveria bassiana chitinase gene - Lomthaisong K. (2014)
This research aims to investigate the effect of Beauveria bassiana chitinase gene on the protein profile of recombinant Escherichia coli by using a proteomic approach. Total protein expressed in non-recombinant E. coli [pSE420] and recombinant E. coli [pDSM1] was analyzed by two-dimensional polyacrylamide gel electrophoresis. The expression profiles of recombinants were then compared with those of non-recombinants. Three protein spots were differentially expressed (2 up-regulate and 1 down-regulate). In addition, five proteins spots were also complementarily observed. Surprisingly, none of these protein spots were clearly unique to the theoretical pI and MW of B. bassiana chitinase. This evidence probably resulted from proteolytic cleavage during the post-translational processing in E. coli host cells. These protein spots were then identified using the TagIdent program. The results suggested that most of these proteins are probably involved in nucleotide biosynthesis.